Predictors of renal damage in systemic lupus erythematous patients: data from a multiethnic, multinational Latin American lupus cohort (GLADEL). Issue 3 (11th December 2020) - Reátegui-Sokolova, Cristina; Ugarte-Gil, Manuel F; Harvey, Guillermina B; Wojdyla, Daniel; Pons-Estel, Guillermo J; Quintana, Rosana; Serrano-Morales, Rosa M; Sacnun, Mónica P; Catoggio, Luis J; Soriano, Enrique R; García, Mercedes A; Saurit, Verónica; et al.
Abstract : Aim: A decrease in proteinuria has been considered protective from renal damage in lupus nephritis (LN), but a cut-off point has yet to be established. The aim of this study was to identify the predictors of renal damage in patients with LN and to determine the best cut-off point for a decrease in proteinuria. Methods: We included patients with LN defined clinically or histologically. Possible predictors of renal damage at the time of LN diagnosis were examined: proteinuria, low complement, anti-double-stranded DNA antibodies, red cell casts, creatinine level, hypertension, renal activity (assessed by the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI)), prednisone dose, immunosuppressive drugs and antimalarial use. Sociodemographic variables were included at baseline. Proteinuria was assessed at baseline and at 12 months, to determine if early response (proteinuria <0.8 g/day within 12 months since LN diagnosis) is protective of renal damage occurrence. Renal damage was defined as an increase of one or more points in the renal domain of The Systemic Lupus International Collaborating Clinics (SLICC)/American College of Rheumatology (ACR) Damage Index (SDI). Cox regression models using a backward selection method were performed. Results: Five hundred and two patients with systemic lupus erythematosus patients were included; 120 patients (23.9%) accrued renal damage during their follow-up. Early response to treatment (HR=0.58), antimalarial use (HR=0.54) and a high SES (HR=0.25) were protective of renal damage occurrence, whereas male gender (HR=1.83), hypertension (HR=1.86) and the renal component of the SLEDAI (HR=2.02) were risk factors for its occurrence. Conclusions: Early response, antimalarial use and high SES were protective of renal damage, while male gender, hypertension and higher renal activity were risk factors for its occurrence in patients with LN.